Answers

2014-05-18T20:51:27+05:30
Lim      {(a^x + b^x + c^x)/3}^2/x
x----->0                                                        
= lim       (2/x){(a^x + b^x + c^x)/3 - 1}            [lim   f(x)^g(x)   =     lim g(x){f(x) -1}]
x------.>0                                                      x-->0                      x--->0
= 2/3 lim       {(a^x -1)/x + (b^x - 1)/x + (c^x -1)}        {if lim f(x) = 1 ; lim g(x) = ∞}
x------>0                                                                    x--->0        x---->0
= 2/3 (lna + lnb + lnc)             {lim    (a^x -1)/1 = lna       & so on for b ; c}
= 2/3ln(abc)                            x--->0
1 5 1